Community Behavior in Rural Areas: Washing Hands and Wearing Masks During the Covid - Ni Putu Wiwik Oktaviani; I Komang Suastika; Ni Wayan Trisnadewi; I Made Sudarma Adiputra (GLOBAL HEALTH SCIENCE GROUP, 2021)
The spread of the Covid-19 virus is currently still increasing even though the Covid-19 vaccine has started to be given to the public. The development of Covid -19 cases as of April 20, 2021, totaling 1,614,849 positive cases. The increase in the spread of the virus requires the application of health protocols through hand washing and the wearing of strict masks during the Covid 19 pandemic. Objective:This study aims to determine the description of hand washing behavior and a description of the wear of masks in the Banjar Dinas Muntigunung community, West Tianyar Village, Kubu District, Karangasem Regency in the Covid-19 Pandemic Era. The type of research used in this research is quantitative research with a descriptive exploratory research design. The population of this research is the whole society Banjar Dinas Muntigunung. The sampling technique used in this study is non-probability sampling with simple random sampling technique of 360 people, the available population is made a lottery number then randomized until 360 samples are collected. Data collection is done online. Data analysis was carried out by univariate namely the frequency distribution. The results showed that the average age of respondents was 33 years with the majority of respondents being female, 58.9%, having a history of high school education of 57.8%. The results showed that the majority of respondents had good hand washing behavior, as many as 360 people (100%) and in the use of masks in the good category, 273 people (75.8%). The community is expected to be able to implement and improve hygiene and healthy living habits, especially the behavior of washing hands with soap in running water and using masks when leaving the house or interacting with other people. The results showed that the average age of respondents was 33 years with the majority of respondents being female, 58.9%, having a history of high school education of 57.8%. The results showed that the majority of respondents had good hand washing behavior, as many as 360 people (100%) and in the use of masks in the good category, as many as 273 people (75.8%). The community has good behavior in washing hands and wearing masks during the Covid 19 pandemic.